Proenkephalin improves cardio-renal risk prediction in acute coronary syndromes: the KID-ACS score - Wenzl, Florian A; Wang, Peizhi; Arrigo, Mattia; Parenica, Jiri; Jones, Donald J L; Bruno, Francesco; Tarnowski, Daniel; Hartmann, Oliver; Boucek, Lubos; Lang, Fabian; Obeid, Slayman; Schober, Andreas; et al. (European heart journal, 2025)
BACKGROUND AND AIMS: Circulating proenkephalin (PENK) is a stable endogenous polypeptide with fast response to glomerular dysfunction and tubular damage. This study examined the predictive value of PENK for renal outcomes and mortality in patients with acute coronary syndrome (ACS). METHODS: Proenkephalin was measured in plasma in a prospective multicentre ACS cohort from Switzerland (n = 4787) and in validation cohorts from the UK (n = 1141), Czechia (n = 927), and Germany (n = 220). A biomarker-enhanced risk score (KID-ACS score) for simultaneous prediction of in-hospital acute kidney injury (AKI) and 30-day mortality was derived and externally validated. RESULTS: On multivariable adjustment for established risk factors, circulating PENK remained associated with in-hospital AKI [per log2 increase: adjusted odds ratio 1.53, 95% confidence interval (CI) 1.13-2.09, P = .007] and 30-day mortality (adjusted hazard ratio 2.73, 95% CI 1.85-4.02, P < .001). The KID-ACS score integrates PENK and showed an area under the receiver operating characteristic curve (AUC) of .72 (95% CI .68-.76) for in-hospital AKI and .91 (95% CI .87-.95) for 30-day mortality in the derivation cohort. Upon external validation, KID-ACS achieved similarly high performance for in-hospital AKI (Zurich: AUC .73, 95% CI .70-.77; Czechia: AUC .75, 95% CI .68-.81; Germany: AUC .71, 95% CI .55-.87) and 30-day mortality (UK: AUC .87, 95% CI .83-.91; Czechia: AUC .91, 95% CI .87-.94; Germany: AUC .96, 95% CI .92-1.00), outperforming the contrast-associated AKI score and the Global Registry of Acute Coronary Events 2.0 score, respectively. CONCLUSIONS: Circulating PENK offers incremental value for predicting in-hospital AKI and mortality in ACS. The simple six-item KID-ACS risk score integrates PENK and provides a novel tool for simultaneous assessment of renal and mortality risk in patients with ACS.
Keywords: Male; Biomarkers; Acute kidney injury; lidé středního věku; Prospective Studies; Acute coronary syndromes; prediktivní hodnota testů; Humans; Risk Assessment; Middle Aged; senioři; akutní koronární syndrom; biologické markery; prospektivní studie; hodnocení rizik; mužské pohlaví; rizikové faktory; Female; enkefaliny; Predictive Value of Tests; Proenkephalin; Aged; ženské pohlaví; Enkephalins; Acute Coronary Syndrome; Mortality risk; Protein Precursors; proteinové prekurzory; lidé; Risk prediction; Acute Kidney Injury; akutní poškození ledvin; Risk Factors